2017
DOI: 10.3399/bjgp17x693641
|View full text |Cite
|
Sign up to set email alerts
|

Variations in presentation, management, and patient outcomes of urinary tract infection: a prospective four-country primary care observational cohort study

Abstract: Variation in presentation and management of uncomplicated UTI at a country primary care network level is clinically unwarranted and highlights a lack of consensus concerning optimal symptom control and antibiotic prescribing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
75
3
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(90 citation statements)
references
References 32 publications
7
75
3
1
Order By: Relevance
“…In terms of symptom severity at recruitment, it would be anticipated that those agreeing to participate (and accepting a delayed prescription) might have less severe symptoms; this appears to be the case. In two comparable trials in urine infection the simple sum (SD) of three frequency items (urgency, daytime frequency, and night time frequency) was 9.6 (3.7) (information from authors) [13] and 9.5 respectively [17]. In comparison, in this study the sum of these three frequency items was 7.5 (3.8).…”
Section: Comparison With Literaturecontrasting
confidence: 50%
See 2 more Smart Citations
“…In terms of symptom severity at recruitment, it would be anticipated that those agreeing to participate (and accepting a delayed prescription) might have less severe symptoms; this appears to be the case. In two comparable trials in urine infection the simple sum (SD) of three frequency items (urgency, daytime frequency, and night time frequency) was 9.6 (3.7) (information from authors) [13] and 9.5 respectively [17]. In comparison, in this study the sum of these three frequency items was 7.5 (3.8).…”
Section: Comparison With Literaturecontrasting
confidence: 50%
“…The confirmed frequency of urine infection (32%) was low compared with previous studies using similar entry criteria but this a Group 1, patients who received Uva-ursi and advice to take ibuprofen; Group 2, patients who received Uva-ursi placebo and advice to take ibuprofen; Group 3, patients who received Uva-ursi and no advice to take ibuprofen; Group 4, patients who received Uva-ursi placebo and no advice to take ibuprofen. may reflect changes in presentation in primary care in the UK since a more recent study (POETIC) using similar entry criteria showed comparable frequencies [4,14,16,17]. Despite the low frequency of confirmed infection in routine care the majority of women will still receive antibiotics (90%) and so these results are still generalizable to the majority of women presenting [17].…”
Section: Comparison With Literaturementioning
confidence: 95%
See 1 more Smart Citation
“…Previous successful campaigns to reduce meticillin-resistant Staphylococcus aureus (MRSA) bloodstream infections and Clostridium difficile infections focused on nosocomial risk factors; however, our data suggest that defining appropriate strategies that aim to reduce community and quasi-community associated E coli bloodstream infections might have a greater effect-eg, improved catheter care and improved quality of antibiotic use for UTI management in the community. Recent antibiotic use is the greatest risk factor for subsequent antibiotic-resistant UTIs; 31 many people who are prescribed antibiotics for UTIs might not have bacterial UTIs, 32 and many bacterial UTIs could resolve in a similar timeframe without antibiotics. 33 Improved point-of-care tests that predict the benefit from antibiotics are urgently needed to guide prescribing decisions.…”
Section: Discussionmentioning
confidence: 99%
“…The burden of urinary tract infections is high worldwide (Foxman, 2014). However, field studies to provide more insight into the clinical practice of the outpatient management of UTIs in adults are scarce (Martinez et al, 2007;Llor et al, 2011;Denes et al, 2012;Butler et al, 2017;Dumpis et al, 2018). The main objective of our study was to fill in this gap by assessing empiric antibiotic choice in different lower urinary tract infections (i.e.…”
Section: Discussionmentioning
confidence: 99%